2013
DOI: 10.1210/jc.2012-3682
|View full text |Cite
|
Sign up to set email alerts
|

Low- or High-Dose Radioiodine Remnant Ablation for Differentiated Thyroid Carcinoma: A Meta-Analysis

Abstract: The low dose of 1100 MBq radioiodine activity is sufficient for thyroid remnant ablation as compared to 3700 MBq radioiodine activity with similar quality of life, less common adverse effects, and a shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 33 publications
3
42
2
2
Order By: Relevance
“…elimination of normal thyroid tissue remnant) in order to facilitate initial post-therapy scanning and dynamic restaging, especially where the assessment of Tg levels are concerned, then low 131 I activities provide a practical advantage (limited or no hospital stay with cost reduction) and minimize the risk of side effects, while still achieving high ablation rates. At least 12 prospective studies have shown that an activity of 1110 MBq/30 mCi met certain arbitrary endpoints roughly as effectively as the historically often-used 3700 MBq/ 100 mCi, provided the size of the post-surgically remaining tissue Bremnant^is not too large [49]. A few papers have even reported similar ablation rates using ∼20 mCi [34,50], while in contrast, some report a significantly lower ablation rate at 30 mCi than when using 100 mCi.…”
Section: Does Adjuvant or Therapeutic Rai Administration Improve Clinmentioning
confidence: 99%
“…elimination of normal thyroid tissue remnant) in order to facilitate initial post-therapy scanning and dynamic restaging, especially where the assessment of Tg levels are concerned, then low 131 I activities provide a practical advantage (limited or no hospital stay with cost reduction) and minimize the risk of side effects, while still achieving high ablation rates. At least 12 prospective studies have shown that an activity of 1110 MBq/30 mCi met certain arbitrary endpoints roughly as effectively as the historically often-used 3700 MBq/ 100 mCi, provided the size of the post-surgically remaining tissue Bremnant^is not too large [49]. A few papers have even reported similar ablation rates using ∼20 mCi [34,50], while in contrast, some report a significantly lower ablation rate at 30 mCi than when using 100 mCi.…”
Section: Does Adjuvant or Therapeutic Rai Administration Improve Clinmentioning
confidence: 99%
“…Aunque no existen ventajas en términos de supervivencia, ciertos estudios han demostrado la conveniencia de dosis bajas versus altas en pacientes de bajo riesgo, independientemente del método de estimulación 36 . Cheng, et al 37 analizaron nueve estudios aleatorizados, que incluyeron 2,569 pacientes de bajo riesgo y diferentes métodos de estimulación de TSH (rhTSH y suspensión hormonal). No encontraron diferencias en la eficacia del yodo 131 entre 30 y 100 mCi.…”
Section: Pacientes De Riesgo Bajounclassified
“…Again, the principal consideration in the ablative setting is minimizing toxicity while maintaining a reasonable rate of success (though reasonable and success are both quite subjective, leading to the possibility of controversy). The bulk of the evidence in recent years has focused on reducing the dose in lowrisk patients in whom remnant ablation is indicated, where there is fairly strong support that, for example, 1.1 GBq is as effective as 3.7 GBq, with a lower level of toxicity (15). Indeed, 2 separate randomized studies published in 2012 showed essentially equivalent ablation success rates whether patients were treated with 1.1 or 3.7 GBq (and whether thyroid hormone withdrawal or recombinant human thyroid-stimulating hormone was used for stimulation); the low-dose group experienced fewer adverse events (16,17).…”
Section: Dose Selectionmentioning
confidence: 99%